Institutional Ownership And Dividend Payout Policy In Kenya - Kibet Koskei Buigut (Journal of Business and Management Review, 2023)
This purpose of this study is to investigate the effect of institutional ownership on dividend payout policy among listed firms in Kenya. The study used a sample of 40 Kenyan listed firms over the period of 2009-2019 collected from published audited financial statements. To test the hypothesized relationships, this study used the fixed effect and random effect panel data. The study used a sample of 40 Kenyan listed firms over the period of 2009-2019 collected from published audited financial statements. To test the hypothesized relationships, this study used the fixed effect and random effect panel data. The empirical findings indicate that foreign and domestic institutional ownerships are significant and positively associated with dividend payout policy